Research on thermoforming process of WE43 rare earth magnesium alloy plate - Hongjiao Qiao; Sheng Lei; Shaojie Cui; Xia Li; Xinru Qin; Houmin Wang (Discover Applied Sciences)
Abstract To investigate the rheological behavior of WE43 magnesium alloy sheets under elevated temperatures (room temperature to 400 °C), uniaxial thermal tensile tests were conducted using a Gleeble-3800 thermal simulation system. The mechanical properties, including yield strength (Rp0.2), tensile strength (Rm), and elongation, were quantitatively analyzed. Results demonstrated a temperature-dependent transition in fracture mechanisms: from brittle to ductile failure as temperature increased, accompanied by significant reductions in yield strength (from 151.1 MPa to 78.1 MPa, a 48.3% decline) and tensile strength (from 220.9 MPa to 88.7 MPa, a 59.8% decrease). Microstructural analysis of fracture surfaces revealed enlarged and homogenized dimples at higher temperatures, alongside grain coarsening from 17.97 μm (room temperature) to 22.90 μm (400 °C), corroborating enhanced plasticity. XRD phase analysis confirmed no substantial phase changes across temperatures, while microhardness peaked at 100.62 HV0.2 (200 °C) due to twinning, followed by a decline as twinning diminished and grains coarsened. This study establishes a quantitative correlation between thermal conditions, mechanical properties, and microstructural evolution, providing critical insights for optimizing hot-forming processes and numerical modeling of WE43 alloy sheets. The findings advance the understanding of temperature-driven plasticity mechanisms and inform strategies for alloy design and industrial applications.